The kite runner - Horberg, William; Parkes, Walter F.; Yeldham, Rebecca; Walsh, E. Bennett; Benioff, David; Forster, Marc, 1969-; Abdalla, Khalid; Ershadi, Homayoun; Toub, Shaun; Leoni, Atossa; Taghmaoui, Said.; Ebrahimi, Zekiria; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2008)
In a divided country on the verge of war, two childhood friends, Amir and Hassan, are about to be torn apart forever. It's a glorious afternoon in Kabul and the skies are bursting with the exhilarating joy of a kite-fighting tournament. But in the aftermath of the day's victory, one boy's fearful act of betrayal will mark their lives forever and set in motion an epic quest for redemption. Now, after twenty years of living in America, Amir returns to a perilous Afghanistan under the Taliban's iron-fisted rule to face the secrets that still haunt him and take one last daring chance to set things right.
Based on the book by Khaled Hosseini.
Special features: commentary with Marc Forster, Khalid Hosseini and David Benioff; words from The kite runner; images from The kite runner; social action PSA; theatrical trailer.
Director of photography, Roberto Schaefer ; editor, Matt Chesse ; music, Alberto Iglesias ; costume designer, Frank L. Fleming ; production designer, Carlos Conti.
Khalid Abdalla, Homayoun Ershadi, Shaun Toub, Atossa Leoni, Said Taghmaoui, Zekiria Ebrahimi, Ali Danish Bakhtyari, Ahmad Khan Mahmoodzada, Nabi Tanha, Elham Ehsas, Bahram Ehsas, Tamim Nawabi, Oadir Farookh, Abdul Salam Yusoutzai.
MPAA rating: PG-13; strong thematic material including sexual assault of a child, violence, and brief strong language.
DVD ; Region 1 ; widescreen presentation ; Dolby Digital 5.1 surround.
Keywords: Male friendship -- Drama; Social classes -- Drama; Betrayal -- Drama; Boys -- Drama; Betrayal; Boys; Male friendship; Social classes; Kabul (Afghanistan) -- Drama; Afghanistan -- Drama; Afghanistan; Afghanistan -- Kabul; Thriller -- Feature; Feature films; Suspense films; Film adaptations; Video recordings for the hearing impaired; Fiction films; Feature films; Drama; Feature films; Fiction films; Film adaptations; Video recordings -- for the hearing impaired